(untitled) (Academicia Globe: Inderscience Research, 2022)
Ancient Kesh has a long and rich history. This region, which is one of the largest areas of the Kashkadarya oasis, has been an important political, economic-social, ethnic and cultural region in the Central Asian civilization throughout its long history. Therefore, the study of the geographical location of the Kesh oasis, the lifestyle of its inhabitants, economic and social life, and the structure of this oasis is of great importance in illuminating the stages of the history of Central Asia.